Patient-specific modeling of hemodynamic characteristics associated with the formation of visceral artery aneurysms at uncommon locations - Li, Siting; Sun, Xiaoning; Chen, Mengyin; Ma, Tianxiang; Liu, Xiao; Zheng, Yuehong (Frontiers in Cardiovascular Medicine, 2022)
Objective Hemodynamic characteristics play critical roles in aneurysm initiation and growth. This study aims to explore the effect of common hemodynamic parameters on the formation of visceral artery aneurysms (VAAs), especially those from the pancreaticoduodenal arteries or other uncommon locations, using real patients’ models. Methods Three-dimension vessel models of 14 VAAs from 13 patients were selected and constructed from computed tomography angiography (CTA) images. Aneurysms were manually removed to perform computational fluid dynamics (CFD) simulations of the models before aneurysm formation. Flow field characteristics were obtained and compared at the aneurysm forming and para-aneurysm areas. Aneurysm forming models were categorized into high-wall-shear stress (WSS) and low-WSS groups according to WSS value at aneurysm forming versus para-aneurysm areas. Results Computational fluid dynamics analysis revealed that the high WSS group had significantly higher WSSmax (P = 0.038), higher time average WSS (TAWSS) (P = 0.011), higher WSS gradient (WSSG) (p = 0.036), as well as lower oscillatory shear index (OSI) (P = 0.022) compared to the low WSS group. Significant higher WSSmax (P = 0.003), TAWSS (P = 0.003), WSSG (P = 0.041) and lower OSI (P = 0.021) was observed at the aneurysm forming site compared to both upstream and downstream areas. Conclusion Both local increase and decrease of WSS and WSS gradient were observed for the visceral artery aneurysm forming area. Computational fluid dynamics analysis could shed light on the pathogenesis of visceral artery aneurysms at uncommon vessel locations.